Promoting University–Industry collaboration in Malaysia: stakeholders’ perspectives on expectations and impediments - Norzaini Azman; Morshidi Sirat; Vincent Pang; Lai, Yew Meng; Anantha Raman Govindasamy; Wardatul Akmam Din (Routledge, 2018)
University–Industry Collaboration (UIC) has been identified as an essential item on Malaysia’s agenda for transforming itself intoknowledge and innovation-based economy. However, despite the efforts, most initiatives have had limited results. This paper reports on an explorative study that sought to understand the contemporary realities of UIC in the Malaysian context. In particular, the study identified the expectations and impediments to UIC, from the perspectives of three groups of stakeholders – the academics, the industry players and policymakers. The findings reveala number of barriers, including cultural differences, perceived lack of academic expertise and reputation, an inadequacy of institutional policies and regulations, lack of trust, issues of intellectual property rights, and the lack of an appropriate reward system. Thispaper concludes by proposing policy recommendations and strategiesthat could be used by the government, university, and the industry to promote further and foster university-industry collaborativeopportunities and initiatives.